Hong Kong and British culture, 1945-97 - Hampton, Mark, 1970- (Book collections on Project MUSE., 2016)
A major contribution to the scholarship on British decolonisation, the cultural history of imperialism and Britain's engagement with China, this highly original study places the emergence of contemporary Hong Kong in a wider post-imperial setting.